The Difference of Masticatory Performance between Body Mass Index Categories on Students of Universitas Sriwijaya - Shanty Chairani; R Irwin Setiadi; Rani Purba (Sriwijaya Journal of Dentistry, 2023)
Introduction: Mastication is a complex rhythmical activity that requires coordination of the neuro-musculature to prepare the food for swallowing. Masticatory performance can be influenced by some factors, such as bite force. Underweight and overweight/obese persons had reported having low bite force. The purpose of this study was to compare the masticatory performance between underweight, normal weight, and overweight/obese adults. Methods: In this cross-sectional study, 60 students of Universitas Sriwijaya were included (age: 21-25 years). Subjects were grouped according to their BMI: group I (underweight), group II (normal weight), and group III (overweight/obese). Masticatory performance was evaluated with the sieves method. During the masticatory performance test, subjects were asked to chew 3-gram peanuts for 20 masticatory strokes, which was done three times. Peanut particles that had been chewed were filtered with a sieve. The volume of peanut particles passed through the sieve was divided by the volume of total particles and multiplied by 100 percent, which the result was noted as a masticatory performance score. The One-way ANOVA test was employed to identify differences between groups. P values ≤0.05 were considered statistically significant. Results: The underweight group showed the smallest masticatory performance score, followed by the overweight/obese group, while the normal weight group showed the highest score. There was a significant difference in masticatory performance score between the underweight and normal weight group (p<0,05), while the rest were not showed a significant difference (p>0,05). Conclusion: The underweight and overweight/obesity groups had a lower masticatory performance compared to the normal weight group.